Enhanced electrocatalytic nitrogen reduction activity by incorporation of a carbon layer on SnS microflowers. Issue 39 (5th October 2020) - Yu, Weikang; Shu, Fenghao; Huang, Yifeng; Yang, Fangqi; Meng, Qiangguo; Zou, Zhi; Wang, Jun; Zeng, Zheling; Zou, Guifu; Deng, Shuguang
Abstract : We report that incorporating a hydrophobic carbon layer can greatly boost the NRR activity of SnS. The C layer limits proton availability at the electrode surface while integrating the advantages of strong N2 adsorption, better conductivity, and improved NRR performance. Abstract : Earth-abundant elements are highly desirable electrocatalysts for artificial N2 fixation (NRR). However, most earth-abundant elements are inactive for the NRR, and the competitive hydrogen evolution reaction (HER) causes inferior faradaic efficiency. Thus, facile modification methods to transform an NRR-unfavorable electrocatalyst into its NRR-favorable counterpart are highly demanded. Herein, we present an efficient hydrophobic carbon layer incorporation strategy on tin monosulfide (SnS@C) to greatly boost the NRR activity of SnS. The hydrophobic carbon layer can limit proton availability at the electrode surface while integrating the advantages of strong N2 adsorption and better conductivity that synergistically improve the NRR performance. Specifically, SnS@C delivers a high faradaic efficiency of 14.56% and NH3 yield of 7.95 × 10 −11 mol s −1 cm −2 (24.33 μgNH3 h −1 mgcat −1 ) at −0.5 V versus the reversible hydrogen electrode. It also exhibits durable stability for consecutive electrolysis over 18 h. Adequate control and 15 N isotopic labeling experiments confirm the reliability of N sources. Density functional theory calculations reveal that the superior activity is attributed to the redistribution and bias of electrons between the SnS and carbon-layer interface. This work highlights that the simple hydrophobic carbon layer incorporation strategy could guide the design and modification of advanced NRR catalysts.